Effect of Loan Portfolio Management, Interest Rate Regulation and Financial Performance of Commercial Banks in Kenya - Araka, Hellen (JOOUST, 2022)
In the year 2016 there were changes in interest rate regulation in the banking sector in Kenya. Interest rates were capped at 4 percent by the Central Bank of Kenya and all banks were lending at 14 percent. The Central Bank Rate was at 10 percent. The banks experienced huge applications for loans and the bank’s profits increased although some banks like Stanbic bank, Barclays bank and Equity bank experienced a negative effect as their profits dropped by between 10 to 12 percent and total nonperforming loans grew by 9.1% in 2017 compared to 8.5% in 2016. Despite prudential regulations on loan portfolio, commercial banks still experience poor financial performance (ROA) due to NPLs. The major objective of the study was to investigate the effect of loan portfolio management, interest rate regulation and financial performance of commercial banks in Kenya. The specific objectives were: to investigate the effect of the management of non-performing loans and financial performance of commercial banks in Kenya, to investigate the effect of the management of loan underwriting and financial performance of commercial banks in Kenya, to identify the effect of loan lending policies and financial performance of commercial banks in Kenya and to identify the effect of interest rate regulation on the relationship between loan portfolio management and financial performance of commercial banks in Kenya. The target population comprised of 43 commercial banks registered in Kenya: 43 Bank managers, 43 Credit managers and 43 operations managers drawn from the 43 commercial banks currently operating in Kenya. A census survey and purposive sampling methods were used whereby all the 129 officers selected from these banks were the respondents and 10 deposit taking microfinance were purposively selected for pilot study. The study used descriptive and correlation research designs and the research philosophy used was positivism. The study used questionnaires to collect primary data. Document analysis guide was used to collect secondary quantitative data from the commercial bank’s financial reports for the period 2013 to 2018. The questionnaires which were administered to the respondents were structured. Content validity was used to determine the validity of the research instruments. Reliability of the data collection instrument was established through test re-test method. In data analysis, descriptive and inferential statistics were used. SPSS version 22 software was used to generate descriptive statistics like the mean, standard deviation, variance and frequency distribution. The data was presented in tables. Multiple linear regression analysis was used to analyze data to produce descriptive and inferential statistics. Hypothesis testing was done by multiple linear regression tests. The quantitative results indicated the existence of a significant effect of interest rate regulation on loan portfolio management and financial performance of commercial banks. Non- performing loans had a significant negative effect on financial performance of commercial banks when customers default on loans. Loan underwriting had a significant both negative and positive effect on financial performance of commercial banks while loan lending policies also had a significant both negative and positive effect on financial performance of commercial banks. The moderator variable, interest rate regulation had a significant moderating effect on NPLs, loan underwriting and loan lending policies with ROA as a measure of financial performance of commercial banks. The study concluded that loan portfolio management has a significant both negative and positive relationship with ROA of commercial banks in Kenya. The study recommended that commercial banks should strengthen its loan underwriting processes, use the services of Credit Reference Bureau train credit officers on how to scrutinize customers, diversify loan portfolios and give out loans which have collateral security only to avoid NPLs. The study also recommended that further research be done using interview schedule for customers of commercial banks and stratified sampling method. The significance of the study is that it will assist the management of the banking sector to equip them with strategies of managing loan defaulters. The top management of commercial banks will use the study findings in bank lending policy formulation and review. The study findings will be of beneficial to the government and Central Banks of countries to know how to regulate interest rates in the world. It will also assist the upcoming researchers to do comparative research study in the same area. The study contributes to the body of knowledge as follows: the commercial banks to diversify their loan portfolios to reduce credit risk (NPLS) and increase the Return on Assets. Limit the high exposure to sectors that are impacted by financial crisis like real estate, enhance restricted supervision and governance and put restrictions on credit risk management. Develop risk measurements and risk management techniques to be used before giving out loans to the public, to ensure that customers repay their loans in time.